1997
DOI: 10.1023/a:1006836712011
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previously we showed in an in situ porcine model that the thiadiazinone derivative [+]EMD 60263, a Ca 2+ sensitizer without phosphodiesterase III inhibitory properties, increased contractility more profoundly in stunned than in non-stunned myocardium. This finding was consistent with the observed leftward shifts of the pCa 2+ /Mg 2+ -ATPase curves of isolated myofibrils induced by [+]EMD 60263. The aim of the present investigation was to study the possible involvement of protein kinase C in the mechanism of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…cTnI proteolysis may thus explain part of the dysfunction observed in the stunned myocardium. In subsequent years, proteomic analyses of stunned myocardium and calpain I-incubated cardiac tissue revealed a multitude of protein changes: degradation of multiple structural and sarcomeric proteins (5,72,335,443,470,471,478) and altered posttranslational modifications of sarcomeric proteins (33,68,491). Based on these studies, it can be concluded that reperfusion injury reduces contractility of myofilaments via a myriad of sarcomeric protein changes and contributes to systolic dysfunction of the stunned heart.…”
Section: Acute and Chronic Sarcomere Changes In Ischemic Heart Diseasementioning
confidence: 99%
“…cTnI proteolysis may thus explain part of the dysfunction observed in the stunned myocardium. In subsequent years, proteomic analyses of stunned myocardium and calpain I-incubated cardiac tissue revealed a multitude of protein changes: degradation of multiple structural and sarcomeric proteins (5,72,335,443,470,471,478) and altered posttranslational modifications of sarcomeric proteins (33,68,491). Based on these studies, it can be concluded that reperfusion injury reduces contractility of myofilaments via a myriad of sarcomeric protein changes and contributes to systolic dysfunction of the stunned heart.…”
Section: Acute and Chronic Sarcomere Changes In Ischemic Heart Diseasementioning
confidence: 99%